EDGE INTELLIGENCE FOR SMART CITY DECISION - Upendra Kumar (International Journal of Multidisciplinary Research and Studies, 2021)
The concept of "smart cities" is an innovative one for the urban landscapes of the future. The use of cutting-edge technology with the goal of optimising municipal resources and operations while simultaneously improving the quality of life for citizens is the ultimate objective of the so-called "smart city" movement. It will be important to make advantage of contemporary breakthroughs in information and communication technology, data analysis, and other fields of technology in order to fulfil this ambitious objective. Because smart cities generate naturally enormous amounts of data, recent artificial intelligence (AI) approaches are interesting because of their capacity to transform raw data into meaningful information that can be used to guide decision making. This is important because smart cities are becoming increasingly common (e.g., using live road traffic data to control traffic lights based on current traffic conditions). However, training and providing these artificial intelligence applications is not an easy operation and will need a significant amount of computer resources to accomplish. One kind of sensing device that is utilised often in a variety of applications that are now being developed for the Internet of Things is composed of cameras that are scattered across public locations in order to capture the actions that take place in the monitored regions. This type of device has led to the development of a specialized subset of the Internet of Things that is known as the Internet of Multimedia Things (IoMT) which is also known as the Multimedia Internet of Things (M-IoT) or the Internet of Media Things (IoMT), as proposed in the recent ISO/IEC 23093-1:20202 standard. This subset of the Internet of Things was brought about by the widespread use of devices like these.